2016
DOI: 10.1139/cjz-2015-0198
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic humpback whale (Megaptera novaeangliae) hotspots defined by bathymetric features off western Puerto Rico

Abstract: North Atlantic humpback whales (Megaptera novaeangliae (Borowski, 1781)) are increasing in number, necessitating current data from winter areas for assessing potential interactions with humans. Occurrence patterns of humpback whales wintering off Puerto Rico were investigated to predict where whales aggregate in nearshore areas. Here we describe the relationship between group associations of humpback whales and bathymetric features off western Puerto Rico. Data were collected from 2011 to 2014. Effort consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Explosions produced in coastal environments can generate reverberation lasting 30 s or more, mainly because of scattering of incident sound by bottom irregularities [55]. Little is known about how singers decide when and where to sing, but recent research suggests that bathymetric features are predictive of where singers are likely to be found [49]. In particular, singers are consistently found in shallow waters (< 200 m deep), over harder bottoms that are relatively flat [3, 59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explosions produced in coastal environments can generate reverberation lasting 30 s or more, mainly because of scattering of incident sound by bottom irregularities [55]. Little is known about how singers decide when and where to sing, but recent research suggests that bathymetric features are predictive of where singers are likely to be found [49]. In particular, singers are consistently found in shallow waters (< 200 m deep), over harder bottoms that are relatively flat [3, 59].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, singers are consistently found in shallow waters (< 200 m deep), over harder bottoms that are relatively flat [3, 59]. In Puerto Rico, singers tend to congregate near the edges of shelves [49]. Although both types of environments tend to be highly reverberant [30, 57], the extent to which songs generate sustained reverberant bands is likely to vary considerably as a function of a singer’s position as well as the acoustic features of constituent units within a song [3, 48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mignucci-Giannoni (1998) compared humpback sightings (published and unpublished, up to 1985) off Puerto Rico and the Virgin Islands and found that those whales also prefer shallow, nearshore waters with little slope. A recent study off the western coast of Puerto Rico found that mother-calf pairs were most often found nearshore in shallow water, while singers were found more frequently along the shelf edge than other areas in Mona Passage (MacKay et al, 2016). Depth did not appear to be a factor for the presence of single nonsinging whales (MacKay et al, 2016).…”
Section: Population Structurementioning
confidence: 99%
“…A recent study off the western coast of Puerto Rico found that mother-calf pairs were most often found nearshore in shallow water, while singers were found more frequently along the shelf edge than other areas in Mona Passage (MacKay et al, 2016). Depth did not appear to be a factor for the presence of single nonsinging whales (MacKay et al, 2016).…”
Section: Population Structurementioning
confidence: 99%